Transcendentalism overturned from absolute power of consciousness until the forces of cosmic architectonics - Tymieniecka, Anna-Teresa.; SpringerLink (Online Service). (Dordrecht Springer Netherlands, 2011)
This collection offers a critical assessment of transcendentalism, the understanding of consciousness, absolutized as a system of a priori laws of the mind, that was advanced by Kant and Husserl. As these studies show, transcendentalism critically informed 20th Century phenomenological investigation into such issues as temporality, historicity, imagination, objectivity and subjectivity, freedom, ethical judgment, work, praxis. Advances in science have now provoked a questioning of the absolute prerogatives of consciousness. Transcendentalism is challenged by empirical reductionism. And recognition of the role the celestial sphere plays in life on planet earth suggests that a radical shift of philosophy's center of gravity be made away from absolute consciousness and toward the transcendental forces at play in the architectonics of the cosmos.
Electronic reproduction.
Keywords: Transcendentalism; Electronic books